Differences in non-high density lipoprotein levels, blood pressure and waist circumference between normal-weight obesity, lean, and obese women - Angriani, Winda; Desmawati, Desmawati; Elliyanti, Aisyah (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Normal Weight Obesity (NWO) is a condition characterized by an average Body Mass Index (BMI) with high body fat percentage (BFP≥30%), distinct from individuals with normal BMI and normal body fat (BFP <30%), known as Normal Weight Lean (NWL). NWO is associated with an increased risk of cardiovascular diseases, dyslipidemia, and central obesity. Objectives: Investigate differences in non-high-density lipoprotein (non-HDL) levels, blood pressure, and waist circumference among respondents with NWO, NWL, and obesity.Materials and Methods: The research adopts an observational design with a cross-sectional approach. The respondents, 96 adult women aged 30-45 from Padang City, were selected based on inclusion and exclusion criteria. Measurements included BMI, body fat using Bioelectrical Impedance Analysis (BIA), waist circumference, and blood pressure. Nutritional status determination was employed to differentiate between NWL, NWO, and obesity. Subsequently, blood samples were taken for non-HDL analysis. Analysis of customarily distributed data used one-way ANOVA and post-hoc Bonferroni, while non-normally distributed data were analyzed using Kruskal-Wallis and post-hoc Mann-Whitney.Results: The study revealed that 20 women (20.8%) were classified as having NWO. The study results indicate a significant difference in non-HDL levels among NWL, NWO, and obesity (p-value = 0.015). There were differences in non-HDL levels between NWO and NWL women, as well as between NWL women and those with obesity. Blood pressure analysis showed no significant difference in blood pressure among NWO, NWL, and obesity. There was a difference in waist circumference, with a significant difference between NWL and obesity (p-value <0.05) and NWO and obesity (p-value <0.05). However, there was no significant difference between NWO and NWL (p-value = 1.00).Conclusion: There were differences in non-HDL levels and waist circumference among NWO, NWL, and obese women, but no significant difference in blood pressure was observed among the three groups.Keywords: Normal weight obesity; non-HDL; blood pressure; Waist circumference